An autopsy case of PARK2 due to a homozygous exon 2 deletion of parkin and associated with α‐synucleinopathy. Issue 4 (13th June 2021) - Sakuwa, Mayuko; Adachi, Tadashi; Yoshida, Kentaro; Adachi, Yoshiki; Nakano, Toshiya; Hanajima, Ritsuko
Abstract : Lewy bodies (LBs) are usually detected in patients with idiopathic Parkinson's disease (PD), but there have been few reports of LBs in a familial form of early‐onset PD associated with several mutations in parkin, a gene that encodes a ubiquitin E3 ligase involved in mitochondrial homeostasis, being also known as PARK2 . Here, we report a case of PD with a PARK2 mutation characterized by a homozygous deletion of exon 2 and incidental LB pathology. A 60‐year‐old man developed tremor in the upper limbs. Although levodopa was initially effective, his symptoms slowly progressed. His cardiac uptake of 123 I‐metaiodobenzylguanidine, as assessed by myocardial scintigraphy, decreased from an early stage after the onset. At the age of 81 years, he developed Legionella pneumonia and died of respiratory failure. Histopathological examination revealed a moderate loss of pigmented neurons, as well as gliosis in the substantia nigra and the locus coeruleus. Little LB‐related pathology was found in the locus coeruleus, dorsal nucleus of vagal nerve, and basal nucleus of Meynert. The cardiac sympathetic nerve in the epicardium showed a reduction in the numbers of fibers immunoreactive for tyrosine hydroxylase and phosphorylated neurofilament protein. Genetic analysis of frozen brain materials revealed a homozygous deletion of exon 2 of parkin . To our knowledge, this is the first autopsy case with a homozygous deletion of exon 2 of parkin . The number of LBs was small, the age of disease onset was later than that in typical PARK2 ‐associated PD patients, and cardiac sympathetic denervation was also present. Thus, we considered the LBs in our case as incidental and preclinical α‐synucleinopathy.